A strontium isoscape of north‐east Australia for human provenance and repatriation. Issue 3 (5th March 2019) - Adams, Shaun; Grün, Rainer; McGahan, David; Zhao, Jian‐Xin; Feng, Yuexing; Nguyen, Ai; Willmes, Malte; Quaresimin, Michael; Lobsey, Brett; Collard, Mark; Westaway, Michael C.
Abstract: It has been estimated that up to 25% of Indigenous human remains held in Australian institutions are unprovenanced. Geochemical tracers like strontium isotope ratios ( 87 Sr/ 86 Sr) have been used globally for over 40 years to discern human provenance and provide independent data to aid in repatriation efforts. To reliably apply this technology, landscape 87 Sr/ 86 Sr isotope ratio variability must be quantified. In Australia, only a few studies have used this technique and they are lacking in detail. Here, we present Australia's first regional strontium isotope ratio variability study. We measured strontium isotope ratios in soil, plant, water, and faunal material throughout Cape York, Queensland, the most northerly point of mainland Australia. Results show a close correlation between surface soil leachates, vegetation, surface water, and faunal 87 Sr/ 86 Sr results with extremely high values (0.78664) associated with ancient Precambrian geology. Our study suggests that measuring 87 Sr/ 86 Sr in soil and plant samples offer a reliable approach for assessing regional Sr isotope distribution, although the inclusion of mammal and freshwater samples is also important to assess exogenous inputs. This study provides an important tool for modern and prehistoric provenance studies and may aid in answering some of Australia's most enduring archaeological questions.